Interior Revitalization of the Former SMP Negeri 13 Widuran Surakarta into the Surakarta City KONI Office with a Sidomukti Batik Theme - Wijayanto, Ananda Wibi (Pendhapa, 2024)
The interior revitalization of the former SMPN 13 Widuran Surakarta into the Surakarta City KONI Office, with an integration of the Sidomukti Batik theme, seeks to preserve and rejuvenate the cultural heritage of the historic building while adapting it for contemporary use. The current underutilization of the building’s facilities and its inadequate spatial atmosphere have been identified as significant detriments to user experience and efficiency. This study adopts the Pamudji Suptandar design methodology, which involves three critical phases: data input, analytical synthesis, and design output. Through this structured approach, the project aims to achieve a balanced restoration that respects the building's historical integrity while providing a functional and aesthetically pleasing office environment. The findings are expected to offer valuable insights and practical applications for interior designers, particularly in the area of revitalizing cultural heritage interiors to meet modern demands without compromising their historical value.